Implementasi Penguatan Nilai-Nilai Profil Pelajar Pancasila Melalui Kegiatan Pramuka - Romadhon, Romadhon; Widijatmoko , Engelbertus Kukuh; Indriani , Noor Desyta (Penerbit STKIP PGRI Bangkalan, 2022)
The implementation of Strengthening Character Education at this time is an inseparable part in every school. The Covid-19 pandemic is a very laudable impact for most educators. The consequences of the Covid-19 Pandemic itself for the world of education in addition to a decrease in grades are also a decrease in the character of students. With these conditions, it is very necessary to strengthen character education to improve the character of students who are starting to decline. One of the right ways is through Scouting activities. In the research that has been carried out, it has a function to find out about strengthening the values ​​of the Pancasila Student Profile through the participation of scouting activities. The approach used for this research is descriptive qualitative which is useful for knowing in depth the implementation of strengthening carried out. The strategies used in gathering information are perception (observation), question and answer (interview), and documentation (documentation). Triangulation of data sources is a method used to obtain data validity. The implementation of Pancasila Student Profile values ​​has been applied in accordance with the attitude assessment, namely spiritual attitudes and social attitudes. The Covid-19 pandemic has an impact on student discipline which is also an obstacle in implementing the values ​​of the Pancasila Student Profile. The reinforcement carried out through scouting activities is able to improve the attitudes of students who are starting to decline, because it has an imprinting effect on students, so that they are able to shape the character of students in accordance with the Pancasila Student Profile, namely character building.